Biomarkers to Improve Diagnosis and Monitoring of Obstructive Sleep Apnea Syndrome: Current Status and Future Perspectives - Konstantinos Archontogeorgis; Evangelia Nena; Nikolaos Papanas; Paschalis Steiropoulos (Pulmonary Medicine)
Obstructive sleep apnea syndrome (OSAS) is characterized by recurrent episodes of upper airway collapse associated with oxygen desaturation and sleep disruption. It is proposed that these periodic changes lead to molecular variations that can be detected by assessing serum biomarkers. Studies have identified inflammatory, oxidative, and metabolic perturbations attributable to sleep-disordered breathing. Given that OSAS is associated with increased cardiovascular and cerebrovascular morbidity, the ideal biomarker should enable timely recognition with the possibility of intervention. There is accumulating data on the utility of serum biomarkers for the evaluation of disease severity, prognosis, and response to treatment. However, current knowledge is limited by data collection techniques, disease complexity, and potential confounding factors. The current paper reviews the literature on the use of serum biomarkers in OSAS. It is concluded that the ideal serum biomarker still needs to be discovered, while caution is needed in the interpretation of hitherto available results.